Efektivitas Penggunaan Media Alat Peraga â€œPerahu Rakitâ€ dan Laboratorium Maya pada Materi Hukum Archimedes - Fatimatuz Zahro; Tri Suci Ambarwati; Jijah Septianingrum (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2022)
The learning Media used today is sophisticated because it utilizes information technology. However, simple teaching aids still remain relevant in science learning. The purpose of this study is to determine the validity of the props that have been made, namely props